Habitual Physical Activity and Plasma Metabolomic Patterns Distinguish Individuals with Low vs. High Weight Loss during Controlled Energy Restriction. Issue 4 (28th January 2015) - Piccolo, Brian D; Keim, Nancy L; Fiehn, Oliver; Adams, Sean H; Van Loan, Marta D; Newman, John W
Abstract: Background: Total weight loss induced by energy restriction is highly variable even under tightly controlled conditions. Identifying weight-loss discriminants would provide a valuable weight management tool and insights into body weight regulation. Objective: This study characterized responsiveness to energy restriction in adults from variables including the plasma metabolome, endocrine and inflammatory markers, clinical indices, body composition, diet, and physical activity. Methods: Data were derived from a controlled feeding trial investigating the effect of 3–4 dairy product servings in an energy-restricted diet (2092 kJ/d reduction) over 12 wk. Partial least squares regression was used to identify weight-loss discriminants in 67 overweight and obese adults. Linear mixed models were developed to identify discriminant variable differences in high- vs. low-weight–loss responders. Results: Both pre- and postintervention variables ( n = 127) were identified as weight-loss discriminants (root mean squared error of prediction = 1.85 kg; Q 2 = 0.43). Compared with low-responders (LR), high-responders (HR) had greater decreases in body weight (LR: 2.7 ± 1.6 kg; HR: 9.4 ± 1.8 kg, P < 0.01), BMI (in kg/m 2 ; LR: 1.0 ± 0.6; HR: 3.3 ± 0.5, P < 0.01), and total fat (LR: 2.2 ± 1.1 kg; HR: 8.0 ± 2.1 kg, P < 0.01). Significant group effects unaffected by the intervention were determined for the respiratory exchange ratio (LR: 0.86 ± 0.05; HR: 0.82 ± 0.03, P < 0.01), moderate physical activity (LR: 127 ± 52 min; HR: 167 ± 68 min, P = 0.02), sedentary activity (LR: 1090 ± 99 min; HR: 1017 ± 110 min, P = 0.02), and plasma stearate [LR: 102, 000 ± 21, 000 quantifier ion peak height (QIPH); HR: 116, 000 ± 24, 000 QIPH, P = 0.01]. Conclusions: Overweight and obese individuals highly responsive to energy restriction had accelerated reductions in adiposity, likely supported in part by higher lipid mobilization and combustion. A novel observation was that person-to-person differences in habitual physical activity and magnitude of weight loss were accompanied by unique blood metabolite signatures. This trial was registered at clinicaltrials.gov as NCT00858312.